2021
DOI: 10.1111/jcmm.16857
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 2 plays a central role in renal tubular mitochondrial dysfunction and kidney ageing

Abstract: Kidney is one of the most important organs in maintaining the normal life activities. With the high abundance of mitochondria, renal tubular cell plays the vital role in functioning in the reabsorption and secretion of kidney. Reports have shown that mitochondrial dysfunction is of great importance to renal tubular cell senescence and subsequent kidney ageing. However, the underlying mechanisms are not elucidated. Cannabinoid receptor 2 is one of the two receptors responsible for the activation of endocannabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Our previous study found that β-catenin plays a central role in mitochondrial dysfunction and renal tubular senescence ( Luo et al, 2018 ; Miao et al, 2019 ). To further study the downstream signals of CXCR2, we pretreated HKC-8 cells with ICG-001 ( Yahong Liu et al, 2020 ; Zhou et al, 2021 ), an inhibitor of β-catenin. HKC-8 cells were pretreated with ICG-001, and then transfected with CXCR2 expression plasmid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study found that β-catenin plays a central role in mitochondrial dysfunction and renal tubular senescence ( Luo et al, 2018 ; Miao et al, 2019 ). To further study the downstream signals of CXCR2, we pretreated HKC-8 cells with ICG-001 ( Yahong Liu et al, 2020 ; Zhou et al, 2021 ), an inhibitor of β-catenin. HKC-8 cells were pretreated with ICG-001, and then transfected with CXCR2 expression plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial dysfunction not only leads to energy absence, but also results in the production of ROS, contributing to DNA damage and cellular senescence ( Di Micco et al, 2021 ). Our previous study showed that the activation of β-catenin was highly involved in mitochondrial dysfunction and cellular senescence, suggesting the close relationship between β-catenin and mitochondrial dysfunction ( Miao et al, 2021 ; Zhou et al, 2021 ). One of the underlying mechanisms lies in the modulation of β-catenin on PGC-1α, a master controller for mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies in small animals are still scarce, there is growing evidence that endocannabinoid-like ALIAmides play key roles in the health of different body organs, such as the gastrointestinal tract [ 113 , 114 ] and the nervous system [ 32 , 34 , 37 ], as well as the upper and lower urinary tract [ 115 , 116 , 117 , 118 ] and the musculoskeletal system [ 97 , 119 , 120 ]. In addition, the deep involvement of ALIAmides in obesity-induced metainflammation is becoming increasingly evident [ 69 , 113 , 121 , 122 , 123 ].…”
Section: Preclinical and Clinical Results In Small Animalsmentioning
confidence: 99%
“…These changes might be related to large differences in the systemic use of amino acids and intermediary metabolism. Recently, the upregulation of the CB2 receptor was found to play a primary role in the mitochondrial dysfunction of renal tubular cells [ 62 ]. Thus, understanding the full extent of differences in eCBs and OxLs in the present study helps identify the relationship between dietary PUFAs and these bioactive lipids in the HDPs.…”
Section: Discussionmentioning
confidence: 99%